Oatmeal porridge: impact on microflora-associated characteristics in healthy subjects - Valeur, Jørgen; Puaschitz, Nathalie G.; Midtvedt, Tore; Berstad, Arnold (British journal of nutrition, 2016)
Oatmeal porridge has been consumed for centuries and has several health benefits. We aimed to investigate the effect of oatmeal porridge on gut microflora functions. A total of ten healthy subjects ingested 60 g oatmeal porridge daily for 1 week. The following microflora-associated characteristics were assessed before and after the intervention: intestinal gas production following lactulose ingestion, faecal excretion of SCFA and faecal levels of urease and β-galactosidase. In addition, rectal levels of PGE2 were measured. Microbial fermentation as evaluated by intestinal gas production and excretion of SCFA did not change significantly following the dietary intervention. However, faecal levels of β-galactosidase and urease decreased after eating oatmeal porridge (P=0·049 and 0·031, respectively). Host inflammatory state, as measured by rectal levels of PGE2, also decreased, but the change was not significant (P=0·168). The results suggest that oatmeal porridge has an effect on gut microbial functions and may possess potential prebiotic properties that deserve to be investigated further.